Organoselenium chemistry-based polymer synthesis - Li, Qilong; Zhang, Yuanyuan; Chen, Zijun; Pan, Xiangqiang; Zhang, Zhengbiao; Zhu, Jian; Zhu, Xiulin (Organic chemistry frontiers an international journal of organic chemistry, 2020)
Due to their unique properties, selenium-containing polymers have become one of the research focuses of polymer materials in recent years. First, selenium can transform among various states of selenoxide, selenone, and selenium free radicals, and then be restored under these conditions, which endows these polymers with multiresponsive behaviors, including responses to redox changes, light, radiation, etc. Second, these polymers show characteristic properties. Selenium-containing polymers exhibit unique multiple optical–electrical characteristics, including high photoconductivity, anisotropic thermoconductivity, high piezoelectric and thermoelectric responses, and a high refractive index. Based on these various properties, selenium-containing polymers are regarded as excellent functional polymer materials. Therefore, it is meaningful to synthesize selenium-containing polymers with various structures. This paper principally gives a summary of the organic reactions of organoselenium compounds and reviews the research on the synthesis of selenium-containing polymers via different methods, such as the use of selenium-containing monomers and their polymerization, selenium-containing initiators for polymerization, selenium-containing mediators for controlled polymerization and selenium-containing molecules for the postmodification of polymers. Moreover, applications of selenium-containing polymers are described, including their use as intrinsic high refractive index polymeric materials, oxidative- and reductive-responsive materials, dynamic exchanging polymers, selective metal adsorbents, and catalysts.